1998
DOI: 10.1021/jp981466v
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Study of the Reaction Ar + HCN → Ar + H + CN

Abstract: A dynamics study of the reaction Ar + HCN f Ar + H + CN for a wide range of initial vibrational and translational energies is reported. All calculations have been carried out with the quasiclassical trajectory method and a realistic potential energy surface for ArHCN. An attempt is made to reproduce the thermal rate coefficient for the reaction. Agreement with experiment is found to be good, and the limitations of the approach are stressed. A brief analysis of rotational effects, energy transfer, and unimolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…7 The calculated thermal rate constant was found to be in good agreement with experiment. As the DMBE surface was not found as much good for the bound states of the system, a global ES potential function was then considered by the authors.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…7 The calculated thermal rate constant was found to be in good agreement with experiment. As the DMBE surface was not found as much good for the bound states of the system, a global ES potential function was then considered by the authors.…”
Section: Introductionsupporting
confidence: 63%
“…With heavier members of the Rg-HCN series, for example, the Ar-HCN, a deeper well with a linear global minimum of about -85.0 and -173.1 cm -1 , respectively, at about 4.63 Å was found by the ES and DMBE methods, 7,8 respectively. Toczylowski et al 15 found it at 147.0 cm -1 at 4.5 Å.…”
Section: Potential Wellmentioning
confidence: 96%
See 2 more Smart Citations
“…Sometimes the latter should be considered predissociative because they may dissociate prior to the collision with argon. However, a rigorous predissociation criterion cannot be easily established and, hence, it may be assumed that all trajectories initiated with internal energies above the threshold should be discarded from the final statistical analysis; for example, a similar procedure has been adopted by Rodrigues and Varandas 43 in the Ar + HCN collision-induced dissociation. Of course, this criterion for defining predissociative trajectories (hereafter referred to as PD1) should be regarded as an approximation because highly energized CH 4 / species may last for a sufficiently long period so that a collision with argon is able to occur.…”
Section: Trajectory Analysismentioning
confidence: 99%